2000
DOI: 10.1007/s004280000322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of loss of heterozygosity and microsatellite instability in adenocarcinomas of the distal esophagus and proximal stomach

Abstract: Adenocarcinoma of the gastroesophageal junction is rapidly rising in incidence. It has been proposed that these tumors be classified as three different types: distal esophageal (AEG I), cardia (AEG II), and subcardia (AEG III). Using comparative genomic hybridization (CGH) analysis, one recent study reported that the 14q chromosomal arm showed a significantly higher rate of deletion in esophageal than in cardia adenocarcinoma. Using a microsatellite analysis technique, we analyzed this area and regions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
0
14
2
Order By: Relevance
“…Investigation of loss of heterozygosity (LOH) is an important tool to detect potential losses of tumor suppressor genes which can characterize different kind of cancers. We and others tried to differentiate adenocarcinomas of the esophagus and gastric cardia according to their LOH pattern, but no significant differences could be identified between the two tumors [56,57]. While van Dekken et al found a significant difference at locus 14Q using comparative genomic hybridization [58], this could not be confirmed in other studies.…”
Section: Genetic Changesmentioning
confidence: 96%
“…Investigation of loss of heterozygosity (LOH) is an important tool to detect potential losses of tumor suppressor genes which can characterize different kind of cancers. We and others tried to differentiate adenocarcinomas of the esophagus and gastric cardia according to their LOH pattern, but no significant differences could be identified between the two tumors [56,57]. While van Dekken et al found a significant difference at locus 14Q using comparative genomic hybridization [58], this could not be confirmed in other studies.…”
Section: Genetic Changesmentioning
confidence: 96%
“…LOH analysis gives more specific information about changes near putative tumor suppressor genes, as compared with CGH. Only one study directly compared the occurrence of LOH in patients with adenocarcinomas of the distal esophagus and gastric cardia, but no differences were found (20). In the present study, we compared the prevalence of LOH in patients with distal esophageal adenocarcinoma and adenocarcinoma of the gastric cardia.…”
Section: Discussionmentioning
confidence: 72%
“…Several previous studies used comparative genomic hybridization (CGH) to quickly compare all of the chromosomal alleles and this did not show significant changes (36 -38). One study found significantly more loss for locus 14q in patients with esophageal adenocarcinoma using CGH, which could not be confirmed in a subsequent study by LOH analysis (20,23). LOH analysis gives more specific information about changes near putative tumor suppressor genes, as compared with CGH.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The gastric carcinoma revealed an irregular tubular pattern with mild to moderate cellular atypism and nuclear pleomorphism (magnification ·300) elements of ampullary (n=10) and gastric cancer (n=12) at the D14S267 locus (details in Table 1). The reason that D14S267 was chosen for screening comes from the initial deletion mapping of our study and its deletion in 20% of cardiac carcinoma in a prior report (Yanagi et al 2000). Apparent LOH at the locus was detected in one (10%) of the ampullary and two (16.7%) of the gastric cancers (16.7%) tested, respectively (Fig.…”
Section: Loh Analysis At the D14s267 Locus In Sporadic Gastric And Ammentioning
confidence: 92%